EVALUATION OF THE USE OF THE SISKEUDES APPLICATION IN EFFORTS TO IMPROVE THE QUALITY OF VILLAGE FINANCIAL ACCOUNTABILITY (CASE STUDY IN BATU MILA VILLAGE DISTRICT MAIWA KAB. ENREKANG) - Rika Rahma; Darmawan Darmawan; Erma Erma (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2022)
The method used is a qualitative research method. This study aims to determine how the evolution of the use of the Village Financial System Application in Batu Mila Village and the quality of village financial accountability after the application of the Village Financial System Application. Data collection techniques used are observation, interviews, documentation, literature study, internet searching. This study uses the term informant, namely village employees who understand and are directly involved in the process of using the Village Financial System Application and the people of Batu Mila Village who feel the benefits of implementing the application. The data analysis techniques used were data reduction, data presentation, and data conclusion. From the results of the evolution of the use of the village financial system application in Batu Mila Village, it is known that Batu Mila Village regularly updates the village financial system application version every year, this is done so that the village can use existing and improved features or the latest features of the application to support the creation financial reports. Then for the quality of financial accountability in Batu Mila Village, after the implementation of the Village Financial System Application, it was found that there had been an increase due to the implementation of the principles of village financial management and balanced with compliance with applicable regulations when managing existing funds.